2017
DOI: 10.18290/rpsych.2017.20.1-4en
|View full text |Cite
|
Sign up to set email alerts
|

Religious support and religious struggle as predictors of quality of life in alkoholics anonymous: Moderation by duration of abstinence

Abstract: The aim of the study was to analyze the connection between religious comfort and struggle and quality of life in Alcoholics Anonymous. The interaction effect of the length of abstinence and religious variables on the quality of life was tested as well. The participants were 100 members of an Alcoholics Anonymous group. We used the Religious Comfort and Strain Scale by Yali, Exline, Wood, and Worthington and the Quality of Life Questionnaire for Adults by Schalock and Keith. The correlation analysis showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Furthermore, religious struggle, just like the other forms of religiosity, occurs around the world and across different religious groups. Empirical studies confirm the existence of religious problems and tensions among Christians (Bryant and Astin 2008;Büssing et al 2013Büssing et al , 2016Büssing et al , 2017aBüssing et al , b, 2018Carter 2019;Łowicki and Zajenkowski 2017;Szcześniak et al 2019;Zarzycka 2018;Zarzycka et al 2017), Muslims (Abu-Raiya et al 2008, 2015, 2018Ai et al 2003), Jews (Abu-Raiya et al 2016;Pirutinsky et al 2011;Pirutinsky and Rosmarin 2018;Rosmarin et al 2009Rosmarin et al , 2017, Hindus (Benson et al 2011;Exline et al 2017;Simha et al 2013;Tarakeshwar et al 2003), and atheists or agnostic samples (Bradley et al 2016;Sedlar et al 2018).…”
Section: Religious Strugglementioning
confidence: 87%
“…Furthermore, religious struggle, just like the other forms of religiosity, occurs around the world and across different religious groups. Empirical studies confirm the existence of religious problems and tensions among Christians (Bryant and Astin 2008;Büssing et al 2013Büssing et al , 2016Büssing et al , 2017aBüssing et al , b, 2018Carter 2019;Łowicki and Zajenkowski 2017;Szcześniak et al 2019;Zarzycka 2018;Zarzycka et al 2017), Muslims (Abu-Raiya et al 2008, 2015, 2018Ai et al 2003), Jews (Abu-Raiya et al 2016;Pirutinsky et al 2011;Pirutinsky and Rosmarin 2018;Rosmarin et al 2009Rosmarin et al , 2017, Hindus (Benson et al 2011;Exline et al 2017;Simha et al 2013;Tarakeshwar et al 2003), and atheists or agnostic samples (Bradley et al 2016;Sedlar et al 2018).…”
Section: Religious Strugglementioning
confidence: 87%
“…Moreover, religious comfort is positively correlated with satisfaction considered as a component of life quality. Those individuals who perceive faith as a source of strength and rely on God's help report greater well-being (Büssing and Mundle 2009;Zarzycka et al 2017). Conversely, preserving negative feelings of guilt/fear towards God and community decreases life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, results derived from an ongoing nationwide survey in the United States among participants at least 66 years old (Krause 2015) showed that greater religious doubt was associated with less life satisfaction. In the Alcoholics Anonymous group, Zarzycka et al (2017) observed that religious comfort correlated positively with the general assessment of quality of life (r = 0.52, p < 0.001) and life satisfaction (r = 0.41, p < 0.001). Fear/guilt and negative emotions towards God correlated negatively with quality of life (r = −0.29, p < 0.01; r = −0.36, p < 0.001).…”
Section: Life Satisfaction and R/s Strugglesmentioning
confidence: 97%
See 1 more Smart Citation
“…Even after controlling for personality factors, interest in religion, intrinsic and extrinsic-personal religiosity are still reasonably strong predictors of happiness and life satisfaction (Aghababaei 2014). Some authors (Emmons 2005;Krok 2014;ten Kate et al 2017;Zarzycka et al 2017) pointed out that being religious provides a sense of meaning and security, offering an important benefit to satisfaction with life. On the bases of these theoretical and empirical promises, we assumed that religiosity might be an intermediating variable in the relationship between personality traits and life satisfaction.…”
Section: Research Problem and Hypothesesmentioning
confidence: 99%